Disease severity and poor mental health are the main predictors of stigmatization in patients with hidradenitis suppurativa. Issue 3 (2nd March 2021) - Akoglu, Gulsen; Yildiz, Irem; Karaismailoğlu, Eda; Esme, Pelin
Abstract: Hidradenitis suppurativa (HS) causes significant psychological distress in patients. We aimed to investigate the stigmatization level of HS patients and to determine the related physical, social, and psychological factors. A questionnaire with 22 questions about the physical and psychosocial problems related to HS was administered to 29 male and 34 female patients between the ages of 18 and 66 to evaluate the thoughts, emotions, attitudes, and behaviors of patients. Each patient filled Dermatology Life Quality Index, Beck Depression Inventory, Liebowitz Social Anxiety Scale, Body Image Scale, and 6‐item Stigmatization Scale. Hurley classification was used to assess severity of disease. Patients with HS feel stigmatized depending on physical and psychosocial problems caused by the disease. Higher stigmatization scores correlated with higher scores of depression ( r : .437, P < .001), social anxiety ( r : .263, P : .03), and worse life quality ( r : .522, P < .001), and body image perception ( r : .696, P < .001). The degree of stigmatization was closely associated with the presence of painful lesions and disruption of socializing ( P : .021 and .033, respectively). Disease severity ( β : 5.12, P : .003 for moderate disease) and reporting feeling psychologically negatively affected due to HS ( β : 4.26 P : .007) were the two main predictors of stigmatization in patients with HS. Cross‐sectional nature of the study is the limitation. In conclusion, the stigmatization level of patients with HS is strongly related to disease severity and poor mental health.